Enhanced adsorption of malachite green onto carbon nanotube/polyaniline composites. Issue 4 (14th May 2012) - Zeng, You; Zhao, Lijia; Wu, Wendong; Lu, Guixia; Xu, Feng; Tong, Yu; Liu, Wenbin; Du, Jinhong
Abstract: To enhance adsorption of organic dyes like malachite green (MG) onto polymeric absorbents, we prepared carbon nanotube (CNT) filled polyaniline (PANI) composites with large surface areas by simply using entangled CNTs as porous frameworks during PANI polymerization. Adsorption behavior of the CNT/PANI composites in MG solutions was experimentally investigated and theoretically analyzed. The CNT/PANI composites exhibit much higher equilibrium adsorption capacity of 13.95 mg g −1 at an initial MG concentration of 16 mg L −1, increasing by 15% than the neat PANI, which is mainly attributed to large surface areas and strong CNT‐PANI interactions of the composites. In addition, theoretical analyses indicate that the adsorption kinetics and the isothermal process of the composites can be well explained by using the Ho pseudosecond‐order model and the Langmuir model, respectively. In light of their high MG adsorption and easy operation, the CNT/PANI composites have great potential as high‐efficiency adsorbents for removal of dyes from wastewater. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :